Pengaruh Citra Merek dan Harga terhadap Keputusan Pembelian Sepatu Ventela di Kalangan Pemuda Yogyakarta dengan Minat Beli sebagai Variabel Mediasi - Annisa Nuraini; Retno Hartati; Sri Rejeki Ekasasi; Hari Nurweni (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
This study aims to analyze the effect of brand image and price variables on the decision to purchase Ventela shoes among Yogyakarta youth with purchase intention as a mediating variable. This type of research is a quantitative research with a causality survey method. The population in this study were all young people in Yogyakarta who had purchased Ventela shoes. The sample used in this study amounted to 71 people. Sampling was carried out using non-probability sampling technique with purposive sampling method. The survey in this study was carried out by distributing questionnaires through Google Forms. The results of the research were analyzed using PLS-SEM with the help of the SmartPLS 4.0.8.7 application. The results showed that the variable brand image, price, and purchase intention partially had a positive and significant effect on purchasing decisions. This study also found that the brand image and price variables partially had a positive and significant effect on purchase intention, however, the purchase intention variable was unable to mediate the effect of brand image and price variables on purchasing decisions for Ventela shoes among Yogyakarta youth.